Synthetic Lethal Phenotypes Caused by Mutations Affecting Chromosome Partitioning in Bacillus subtilis - Britton, Robert A. (American Society for Microbiology, 1999)
We investigated the genetic interactions between mutations affecting chromosome structure and partitioning in Bacillus subtilis. Loss-of-function mutations in spoIIIE (encoding a putative DNA translocase) and smc (involved in chromosome structure and partitioning) caused a synthetic lethal phenotype. We constructed a conditional mutation in smc and found that many of the spoIIIE smc double-mutant cells had a chromosome bisected by a division septum. The growth defect of the double mutant was exacerbated by a null mutation in the chromosome partitioning gene spo0J. These results suggest that mutants defective in nucleoid structure are unable to move chromosomes out of the way of the invaginating septum and that SpoIIIE is involved in repositioning these bisected chromosomes during vegetative growth.